1998
DOI: 10.1073/pnas.95.3.1289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a neuregulin and protein-tyrosine phosphatase response element in the nicotinic acetylcholine receptor ɛ subunit gene: Regulatory role of an Ets transcription factor

Abstract: At the neuromuscular synapse, innervation induces endplate-specific expression of adult-type nicotinic acetylcholine receptors by selective expression of their subunit-encoding genes (␣ 2 ␤␦) in endplate-associated myonuclei. These genes are specifically regulated by protein-tyrosine phosphatase (PTPase) activity. In addition, neuregulin͞ acetylcholine-receptor-inducing activity, a nerve-derived factor that stimulates nicotinic acetylcholine receptor synthesis, induces adult-type specific subunit gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…For example, the nACHR subunit and utrophin-A promoter N-box play a critical role in regulating expression levels and more importantly in restricting expression to the NMJ (Schaeffer et al, 2001). We and others (Gramolini et al, 1999a;Khurana et al, 1999) have shown that the nerve-derived growth factor heregulin (HRG) causes a N-box-mediated increase in utrophin-A promoter activity via extracellular signal-regulated kinase-dependent activation of the Ets-related transcription factor complex GABP␣/␤, in a manner similar to that noted in the nACHR␦ and nACHR subunit promoters (Falls et al, 1993;Koike et al, 1995;Sapru et al, 1998; This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -12-1069) on May 16, 2007. 1998). Additionally, SP1 (Galvagni et al, 2001;Gyrd-Hansen et al, 2002), NFATc1/calcineurin (Chakkalakal et al, 2003;Chakkalakal et al, 2004), and myogenic factors (Gramolini and Jasmin, 1999;Perkins et al, 2001) can also activate the utrophin-A promoter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nACHR subunit and utrophin-A promoter N-box play a critical role in regulating expression levels and more importantly in restricting expression to the NMJ (Schaeffer et al, 2001). We and others (Gramolini et al, 1999a;Khurana et al, 1999) have shown that the nerve-derived growth factor heregulin (HRG) causes a N-box-mediated increase in utrophin-A promoter activity via extracellular signal-regulated kinase-dependent activation of the Ets-related transcription factor complex GABP␣/␤, in a manner similar to that noted in the nACHR␦ and nACHR subunit promoters (Falls et al, 1993;Koike et al, 1995;Sapru et al, 1998; This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -12-1069) on May 16, 2007. 1998). Additionally, SP1 (Galvagni et al, 2001;Gyrd-Hansen et al, 2002), NFATc1/calcineurin (Chakkalakal et al, 2003;Chakkalakal et al, 2004), and myogenic factors (Gramolini and Jasmin, 1999;Perkins et al, 2001) can also activate the utrophin-A promoter.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5, lane 1, we purified two proteins of 43 and 58 kDa from these nuclear extracts. Because, the molecular masses exactly matched members of the ets-related GABP␣/␤ transcription factors that have been implicated in case of the nACHR genes (Sapru et al, 1998;Schaeffer et al, 1998), we performed immunoblot analysis using affinity-purified antibodies against GABP␣ and GABP␤ on the purified fractions (Brown and McKnight, 1992;de la Brousse et al, 1994), to determine the molecular identity of the purified protein. As shown in Figure 5, lanes 2 and 3, the 43-and (Dennis et al, 1996) and was kind gift from Drs.…”
Section: Gabp␣/␤ Transcription Factors Are Mediators Of Utrophin Actimentioning
confidence: 99%
“…Both nACHR and utrophin proteins are codistributed in adult myofiber mainly at the neuromuscular junction (NMJ) with a secondary peak of enrichment at the myotendinous junction (Khurana et al, 1991). Furthermore, in common with the nACHR ⑀ subunit gene promoter, the utrophin promoter contains an N-box motif (Koike et al, 1995;Dennis et al, 1996), which in the case of the nACHR ⑀ subunit gene is critical for mediating synapse-specific transcription via ets-related transcription factors (Koike et al, 1995;Sapru et al, 1998;Schaeffer et al, 1998). Although the functional relevance of this motif in the utrophin promoter is unclear, its existence coupled with highly regulated distribution of gene product in muscle at the NMJ would suggest that nerve-derived growth factors such as heregulin (cf.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MuSK promoter activity or mRNA was increased in muscle cells stimulated with neuregulin (23,25), a factor that increases AChR expression via the mitogen-activated protein kinase pathways (1,45,46,49). Downstream of mitogen-activated protein kinases is the Ets transcription factor GABP, which appears to be necessary and sufficient for synaptic expression (15,41,43). Transgenic mice expressing a dominant-negative Ets mutant demonstrate alterations in NMJ postsynaptic morphology and decreased expression of genes containing an Etsbinding site; however, the expression of MuSK and Rapsyn was unchanged (11).…”
mentioning
confidence: 99%